Diagnostic value of circulating lncRNAs for gastric cancer: A systematic review and meta-analysis - Li, Jian; Zhang, Yanyan; Xu, Qingyu; Zhang, Yaqiong; Bei, Songhua; Ding, Ying; Zhang, Xiaohong; Feng, Li (Frontiers in Oncology, 2022)
Objective: With the prevalence of the next generation sequencing (NGS) technology, a large number of long non-coding RNAs (lncRNAs) has been attracted tremendous attention and received extensive research in gastric cancer (GC). It was revealed that lncRNAs not only participate the transduction of various singling pathways and thus influencing GC genesis and development, but also have the potential for GC diagnosis. Therefore, we aimed to conduct a meta-analysis on previous studies on GC. Materials and Methods: A electronic search was made before August 2021 on databases including PubMed, Embase, and Web of science. Relevant articles that compare lncRNAs expression in GC patients and healthy controls were summarized. And we conducted meta-analysis with the objective of evaluate the ability of lncRNAs in diagnosing GC. Results: A total of 40 original researches including 6772 participants were discussed in this meta-analysis. The overall sensitivity, specificity and the area under the curve (AUC) were 0.78 (95%CI: 0.75 - 0.81), 0.79 (95%CI: 0.74 - 0.83) and 0.85 (95%CI: 0.81 - 0.87), respectively. The value of pooled diagnostic odds ratios (DOR) was 13.00 (95%CI: 10.00 – 17.00). Conclusions: The circulating lncRNAs can screening GC patients from healthy controls with high diagnostic value and efficiencies, and may serve as a novel potential screening method.